Can an Efficient Metal-Oxide-Semiconductor Device be Made from Aluminium Nitride Ultra-Wide Bandgap Semiconductor? - Chanana, Ravi Kumar (Transactions on Engineering and Computing Sciences, 2023)
The question of whether one can make an efficient metal-oxide-semiconductor (MOS) device using wurtzite Aluminium Nitride semiconductor is answered in this short communication.